A PERSPECTIVE ON THE MANAGEMENT PROCESSES SPECIFIC TO ORGANIC FARMING - Simina, Popescu Anca; Raluca, Călin (The journal of contemporary issues in business and government, 2021)
The evolution of society has attracted positive changes in all fields of activity, implicitly in agriculture, but at the same time the increase in productivity in agriculture has also come with negative consequences, as they have significantly increased the use of fuel for agricultural machinery, electricity for automatic systems. In addition to providing safe and nutritious food, organic production is considered sustainable and protects natural resources and the health of consumers. In this context, the main objective of the research is to analyse the current state of organic food on the Romanian market compared to the European Union by taking into account the main aspects of the market, to identify its weaknesses, challenges and opportunities. For these reasons, we believe that the chosen topic is current, the research team thus assuming an active role in participating in campaigns to promote and inform consumers about the benefits of consuming organic products.